Differences in Some Morphological Characteristics and Body Mass Index in Children of Younger School Age with Reference to Their Gender - Boris Banjevic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2019)
Kinesiologists have long ago noticed the great importance of determining and comparing parameters of growth and development in certain age of school children and youth. The aim of the research is to determine eventual existence of statistically signifi cant diff erences in morphological characteristics and and body mass index with boys and girls of younger school age. The research has been performed on a sample of 60 students divided into two groups: 32 boys and 28 girls from the second and and third grade of the Primary school "Jagos Kontic" from Nikšić. Morphological characteristics were evaluated by a battery of four variables: body height, body weight, waist circumference and hip circumference. The values of the body mass index have been calculated. The signifi cance of the diff erences between gender was determinated by t-test for small independent samples. Signifi cant diff erences have been established in the body height and waist circumference in favour of boys. The obtained data about nourishment based on the body mass index (BMI) indicate a high percentage of normal nutritional status for the complete sample of the examinees. The obtained results of research confi rm the need to perform a more comprehensive research of morphological indicators in this age.